The Role of Islamic Finance and Inflation in Economic Growth: Evidence From Indonesia and Malaysia - Muhammad Yunizar; Muhammad Yasir Yusuf; Khairul Amri (Majapahit Journal of Islamic Finance and Management, 2026)
This study investigates the dynamic relationship within the Finance-Growth Nexus by examining the roles of Islamic Banking Financing (IBF), Sukuk Holding, and Inflation in driving economic growth (GDP) in Indonesia and Malaysia. Utilizing a Panel Vector Error Correction Model (PVECM) on quarterly data from 2015 to 2024, the research identifies both long-run equilibrium paths and short-run transmission mechanisms. The empirical results reveal a stable long-term integration among the variables, with an error correction mechanism adjusting macroeconomic imbalances at a speed of 31.8% per quarter. The findings highlight that IBF acts as a significant catalyst for GDP growth, albeit with a four-quarter gestation period, reflecting the time-intensive nature of asset-backed Sharia contracts. While Sukuk Holding demonstrates short-term neutrality, it emerges as a dominant structural pillar for long-term economic stability. Conversely, Inflation is identified as a significant disruptive factor that hinders growth by distorting the efficiency of profit-sharing transmission. These results suggest that monetary authorities must synchronize Sharia financial deepening with rigorous price stability frameworks to ensure sustainable industrial expansion.